2021
DOI: 10.3390/nu13124395
|View full text |Cite
|
Sign up to set email alerts
|

The Dietary Intake of Carrot-Derived Rhamnogalacturonan-I Accelerates and Augments the Innate Immune and Anti-Viral Interferon Response to Rhinovirus Infection and Reduces Duration and Severity of Symptoms in Humans in a Randomized Trial

Abstract: Acute respiratory infections are an important health concern. Traditionally, polysaccharide-enriched extracts from plants, containing immunomodulatory rhamnogalacturonan-I (RG-1), were used prophylactically. We established the effects of dietary supplementation with carrot-derived RG-I (cRG-I, 0–0.3–1.5 g/day) in 177 healthy individuals (18–65 years) on symptoms following infection with rhinovirus strain 16 (RV16). Primary outcomes were changes in severity and duration of symptoms, and viral load in nasal lava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 45 publications
2
23
0
1
Order By: Relevance
“…It has now become clear that RG-I fibers from various plant sources have a modulating effect on immune function and on the microbiota ( 225 , 226 ). A recent randomized controlled trial explored a low or a higher dose of cRG-I from carrot as a dietary supplement in heathy volunteers ( 227 ). After 8 weeks, the volunteers were infected with a low dose of rhinovirus in their nasal cavity and then the immune response and the development of cold symptoms were monitored.…”
Section: Plant-derived Non-digestible Polysaccharides Microbiota Immu...mentioning
confidence: 99%
See 1 more Smart Citation
“…It has now become clear that RG-I fibers from various plant sources have a modulating effect on immune function and on the microbiota ( 225 , 226 ). A recent randomized controlled trial explored a low or a higher dose of cRG-I from carrot as a dietary supplement in heathy volunteers ( 227 ). After 8 weeks, the volunteers were infected with a low dose of rhinovirus in their nasal cavity and then the immune response and the development of cold symptoms were monitored.…”
Section: Plant-derived Non-digestible Polysaccharides Microbiota Immu...mentioning
confidence: 99%
“…Such studies in which the effect of a nutritional intervention on the course after a (viral) challenge is measured in humans are seen as particularly relevant by experts and regulators ( 228 , 229 ). Consumption of cRG-I was found to greatly accelerate the anti-viral IFN response in infected nasal epithelium and the local innate immune response, resulting in a significantly milder clinical course with less severe and shorter cold symptoms ( 227 ).…”
Section: Plant-derived Non-digestible Polysaccharides Microbiota Immu...mentioning
confidence: 99%
“…This single center, randomized, double-blind, placebo-controlled dose response study had three arms with 0, 0.3 g/day (d) and 1.5 g/d cRG-I in a parallel design. Details on design, adverse events, safety monitoring, disposition of subjects and primary outcome have been described earlier [ 13 ]. The study period comprised four periods: enrolment (screening, eligibility), dietary supplementation for 8 weeks, response to RV16 infection (exposure on day 0, d0) with continued supplementation for 2 weeks, and 3-week follow-up without supplementation ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Recently we demonstrated that dietary intake of carrot-derived RG-I accelerates and augments the innate immune and anti-viral interferon responses to an infection with rhinovirus strain 16 (RV16) and reduces the duration and severity of symptoms in healthy volunteers [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation